Increased Risk of Inflammatory Bowel Disease in Families with Tonsillectomy: A Danish National Cohort Study. Issue 2 (March 2019) - Bager, Peter; Gørtz, Sanne; Feenstra, Bjarke; Nyboe Andersen, Nynne; Jess, Tine; Frisch, Morten; Melbye, Mads
Abstract : Background: The possible etiologic link between tonsillectomy and inflammatory bowel diseases remains unclear. To investigate the hereditary component, we assessed the risk of inflammatory bowel disease after own tonsillectomy as well as after tonsillectomy among family members. Methods: A nationwide Danish cohort of 7, 045, 288 individuals was established and linked to comprehensive national registers with data on kinship, tonsillectomy surgery, and diagnosis of inflammatory bowel disease from all health sectors. We used Poisson regression models to estimate hospital contact rate ratios (RR) for Crohn's disease and ulcerative colitis, with 95% confidence intervals (CI), between individuals with or without tonsillectomy, as well as between individuals with or without tonsillectomized relatives. Results: During 189 million person-years of follow-up between 1977 and 2014, 276, 673 individuals were tonsillectomized, 22, 015 developed Crohn's disease, and 49, 550 developed ulcerative colitis. Rates of inflammatory bowel disease were elevated up to 20 years after own tonsillectomy (Crohn's disease: RR 1.52 [95% CI = 1.43, 1.61]; ulcerative colitis: RR 1.24 [95% CI = 1.18, 1.29]). RRs for Crohn's disease was 1.22 (95% CI = 1.17, 1.27) after first-degree relatives' tonsillectomy, 1.14 (95% CI = 1.08, 1.19) after second-degree relatives' tonsillectomy, and 1.08 (95% CI = 1.01, 1.15) after third-degree relatives' tonsillectomy. Corresponding RRs for ulcerative colitis were 1.10 (95% CI = 1.07, 1.13), 1.05 (95% CI = 1.01, 1.08), and 1.03 (95% CI = 0.98, 1.09). Conclusions: Even individuals with tonsillectomized family members were at increased risk of inflammatory bowel disease. These findings call into question a direct influence of tonsillectomy on gastrointestinal inflammation and point instead toward shared hereditary or environmental factors. See video abstract at, http://links.lww.com/EDE/B464 . Abstract : Supplemental Digital Content is available in the text.